Doprinos akademika Ivana Cvitkovića razvoju sociologije religije / Academician Ivan Cvitković's Contribution to the Sociology of Religion Development - Fočo, Salih (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
This text is a review of the book The Contribution of Academician Ivan Cvitković to the Development of the Sociology of Religion (On the Occasion of His 75th Birthday), edited by Mirko Pejanović, Sarajevo: Academy of Sciences of Bosnia and Herzegovina, 2020.